Effect of Protein O-Mannosyltransferase (MSMEG_5447) on M. smegmatis and Its Survival in Macrophages - Jia, Liqiu; Sha, Shanshan; Yang, Shufeng; Taj, Ayaz; Ma, Yufang (Frontiers in Microbiology, 2021)
Protein O-mannosyltransferase (PMT) catalyzes an initial step of protein O-mannosylation of Mycobacterium tuberculosis (Mtb) and plays a crucial role for Mtb survival in the host. To better understand the role of PMT in the host innate immune response during mycobacterial infection, in this study, we utilized Mycobacterium smegmatis pmt (MSMEG_5447) gene knockout strain, ΔM5447, to infect THP-1 cells. Our results revealed that the lack of MSMEG_5447 not only impaired the growth of M. smegmatis in 7H9 medium but also reduced the resistance of M. smegmatis against lysozyme and acidic stress in vitro. Macrophage infection assay showed that ΔM5447 displayed attenuated growth in macrophages at 24 h post-infection. The production of TNF-α and IL-6 and the activation of transcription factor NF-κB were decreased in ΔM5447-infected macrophages, which were further confirmed by transcriptomic analysis. Moreover, ΔM5447 failed to inhibit phagosome–lysosome fusion in macrophages. These findings revealed that PMT played a role in modulating the innate immune responses of the host, which broaden our understanding for functions of protein O-mannosylation in mycobacterium–host interaction.